1997
DOI: 10.1038/bjc.1997.149
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of charged F(ab')2 photoimmunoconjugates in a xenograft model of ovarian cancer

Abstract: Summary The effect of charge modification of photoimmunoconjugates (PICs) on their biodistribution in a xenograft model of ovarian cancer was investigated. Chlorin.6 e6 was attached site specifically to the F(ab')2 fragment of the murine monoclonal antibody OC125, directed against human ovarian cancer cells, via poly-1-lysine linkers carrying cationic or anionic charges. Preservation of immunoreactivity was checked by enzyme-linked immunosorbent assay (ELISA). PICs were radiolabelled with 1251 and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 21 publications
1
51
1
Order By: Relevance
“…However, these conjugate preparations often contained significant amounts of impurities. A more refined method for conjugation to polymeric cationic and anionic carriers was later developed by Hamblin et al (1996) and was used successfully in vitro and in vivo (Duska et al, 1997). Within these studies, a chlorin e6-NHS ester is used without purification prior to attachment to the macromolecule.…”
Section: Discussionmentioning
confidence: 99%
“…However, these conjugate preparations often contained significant amounts of impurities. A more refined method for conjugation to polymeric cationic and anionic carriers was later developed by Hamblin et al (1996) and was used successfully in vitro and in vivo (Duska et al, 1997). Within these studies, a chlorin e6-NHS ester is used without purification prior to attachment to the macromolecule.…”
Section: Discussionmentioning
confidence: 99%
“…These targeting species include monoclonal antibodies (Duska et al, 1997), lipoproteins (Hamblin and Newman, 1994b), microspheres (Bachor et al, 1991), liposomes (Cuomo et al, 1990) and polymers (Krinick et al, 1994). The latter may be either natural polymers such as dextran (Rakestraw et al, 1990) and polyamino-acids (Goff et al, 1991;Soukos et al, 1997) or synthetic polymers such as N-(2-hydroxypropyl)-methacrylamide (Seymour et al, 1987) and polyvinyl alcohol (Davis et al, 1993).…”
mentioning
confidence: 99%
“…In the NIH-OVCAR-5 human ovarian tumor xenograft, the i.p.-administered positively charged immunoconjugate delivered much higher amounts of chlorin e6 to the tumor tissue than the negatively charged immunoconjugate and a nontargeted immunoconjugate prepared with a nonspecific IgG and free chlorin e6. 78 Multiple intraperitoneal PDT performed at 3 hours after photosensitizer administration (i.p.) in the same tumor model demonstrated that tumor-bearing animals tolerated the repeated PDT treatments well, and tumor responses (residual tumor weight and animal survival time) to the positively charged conjugate were much better than responses to the negatively charged or free chlorin e6.…”
Section: Tumor Surface Proteins or Peptidesmentioning
confidence: 99%